1990
DOI: 10.1093/oxfordjournals.aje.a115666
|View full text |Cite
|
Sign up to set email alerts
|

Epigenesis Theory: A Mathematical Model Relating Causal Concepts of Pathogenesis in Individuals to Disease Patterns in Populations

Abstract: A mathematical modeling approach called epigenesis theory is presented which relates three aspects of pathogenesis to the population distribution of disease. The three aspects of pathogenesis involve how two or more measured variables interact. They are 1) whether the measured variables are related to the same causal action, 2) whether there is only one pathogenic process leading to disease, and 3) whether the measured variables contribute to the same pathogenic process. Epigenesis theory defines the following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 0 publications
0
10
0
2
Order By: Relevance
“…To explore this hypothesis in our study, we modeled renal function by sequentially including endothelial function and CRP in multiple regression analyses. This technique can be used for investigating causal inferences in mechanistic hypotheses (24). It is intriguing that this analysis indicated that CRP is a stronger correlate of renal function and showed that endothelial function loses considerable explanatory power for the creatinine variance when tested in a model that includes both factors, CRP retaining a much stronger association with the outcome measure.…”
Section: Discussionmentioning
confidence: 95%
“…To explore this hypothesis in our study, we modeled renal function by sequentially including endothelial function and CRP in multiple regression analyses. This technique can be used for investigating causal inferences in mechanistic hypotheses (24). It is intriguing that this analysis indicated that CRP is a stronger correlate of renal function and showed that endothelial function loses considerable explanatory power for the creatinine variance when tested in a model that includes both factors, CRP retaining a much stronger association with the outcome measure.…”
Section: Discussionmentioning
confidence: 95%
“…Unfortunately, some of these techniques have been found to provide far more ambiguous evidence on which to base mechanistic conclusions than was first believed. For example, analysis of patterns of joint effects has been proposed as a means of identifying causal structure [1], but simple counterexamples show that in general the underlying etiologic model cannot be readily identified[2]. Typically, some method is proposed under a sound theoretical argument in a specific analytic setting, but this method is subsequently applied in a more general context in which those specific theoretical conditions no longer hold.…”
Section: Introductionmentioning
confidence: 99%
“…Festzuhalten bleibt, dass in der Epidemiologie selten übergeordnete Theorien explizit adressiert werden [48], obwohl sie im Berufsalltag sehr wohl relevant sindangefangen von Theorien zu Selektionsprozessen in Berufspopulationen [44] über Theorien zur Krankheitsverursachung [13,26,47] bis hin zur Ethik [46].…”
Section: Warum Ist Theorie Notwendig?unclassified